Study of the chemical composition of the freon extract of the Damask rose (Rosa damascena Mill.) - Panasenko, O. I.; Odyntsova, V. M.; Denysenko, O. M.; Shkopynska, T. Ye.; Mozul, V. I.; Holovkin, V. V.; Панасенко, Олександр Іванович; Одинцова, Віра Миколаївна; Денисенко, Ольга Миколаївна; Шкопинська, Т. Є.; Мозуль, Валентина Іванівна; Головкін, Володимир В'ячеславович (Запорізький державний медичний університет, 2023)
The aim of this study was to establish the component composition of the freon extract of Damask rose grown in vitro and to substantiate the advantages of this method and the prospects for the use of phytosubstances in medical practice. Materials and methods. The object of the study was the freon extract of Damask rose, grown by the method of clonal micropropagation in vitro. The qualitative and quantitative determination of the components of the freon extract was determined using the chromato-mass spectrometric method. Results. According to the results of the chromato-mass-spectrometric study, 60 compounds were identified, 6 of which were in the isomeric state. The following components prevailed by percentage: рhenylethyl alcohol – 64.070 %, citronellol – 6.090 %, nonadecane – 4.636 %, heneicosane – 2.590 %, geraniol – 1.749 %. Мета роботи – встановити компонентний склад фреонового екстракту троянди дамаської, вирощеної в умовах in vitro, та обґрунтувати переваги цього методу, перспективи використання фітосубстанцій у медичній практиці. Матеріали та методи. Об’єкт дослідження – фреоновий екстракт троянди дамаської, що вирощена методом клонального мікророзмноження в культурі in vitro. Якісне та кількісне визначення компонентів фреонового екстракту здійснили за допомогою хромато-мас-спектрометричного методу. Результати. У результаті хромато-мас-спектрометричного дослідження ідентифіковано 60 сполук, із них 6 в ізомерному стані. За відсотковим вмістом переважали такі компоненти: рhenylethyl alcohol – 64,070 %, сitronellol – 6,090 %, nonadecane – 4,636 %, heneicosane – 2,590 %, geraniol – 1,749 %.
Дослідження хімічного складу фреонового екстракту троянди дамаської (Rosa damascena Mill.)
Panasenko O. I. - ORCID ID: 0000-0002-6102-3455; Odyntsova V. M. - ORCID ID: 0000-0002-7883-8917; Denysenko O. M. - ORCID ID: 0000-0002-0448-4677; Shkopynska T. Ye. - ORCID ID: 0000-0001-7432-1577; Mozul V. I. - ORCID ID: 0000-0002-4099-8042; Holovkin V. V. - ORCID ID: 0000-0001-7787-0969.
Keywords: Rosa damascena Mill.; chromatography-mass spectrometry; chemical composition; хромато-мас-спектрометрія; хімічний склад